The Effector Protein CgNLP1 of Colletotrichum gloeosporioides Affects Invasion and Disrupts Nuclear Localization of Necrosis-Induced Transcription Factor HbMYB8-Like to Suppress Plant Defense Signaling - Yang, Guangyong; Yang, Jie; Zhang, Qiwei; Wang, Wenfeng; Feng, Liping; Zhao, Li; An, Bang; Wang, Qiannan; He, Chaozu; Luo, Hongli (Frontiers in Microbiology, 2022)
Fungi secrete numerous effectors to modulate host defense systems. Understanding the molecular mechanisms by which fungal effectors regulate plant defense is of great importance for the development of novel strategies for disease control. In this study, we identified necrosis- and ethylene-inducing protein 1 (Nep1)-like protein (NLP) effector gene, CgNLP1, which contributed to conidial germination, appressorium formation, invasive growth, and virulence of Colletotrichum gloeosporioides to the rubber tree. Transient expression of CgNLP1 in the leaves of Nicotiana benthamiana induced ethylene production in plants. Ectopic expression of CgNLP1 in Arabidopsis significantly enhanced the resistance to Botrytis cinerea and Alternaria brassicicola. An R2R3 type transcription factor HbMYB8-like of rubber tree was identified as the target of CgNLP1.HbMYB8-like, localized on the nucleus, and induced cell death in N. benthamiana. CgNLP1 disrupted nuclear accumulation of HbMYB8-like and suppressed HbMYB8-like induced cell death, which is mediated by the salicylic acid (SA) signal pathway. This study suggested a new strategy whereby C. gloeosporioides exploited the CgNLP1 effector to affect invasion and suppress a host defense regulator HbMYB8-like to facilitate infection.